Worms in the anthropocene : the multispecies world in Xu Bing’s Silkworm series - Chu, Kiu-Wai (Palgrave Macmillan, 2021)
In a visual art project titled Dear Climate, a group of American artists and scholars designed “a collection of agitprop posters and meditative audio experiences that help you meet, befriend, and become climate change.”i These posters are designed to promote environmental awareness, and particularly, multispecies co-existence in the Anthropocene age, as reflected in posters with slogans such as “BIODIVERSITY IS THE LAND OF OPPORTUNITY”; “PARTY WITH THE BEES IN THE BUTTERFLY BUSH”; “MEET THE BEETLES”; and “SPEND QUALITY TIME WITH AN INSECT.” Human beings encounter insects on a daily basis and yet rarely give them much attention. When they are noticed, they are often exterminated or turned into economic resources for human consumption and utilization. What does it mean to spend quality time with an insect? What is the role of art in cultivating such an attitude in the contemporary world?